Confronting the Challenges of Sports Injuries in Developing Countries: A Focus on Nepal. - Joshi, Amit; Regmi, Subhash (Nepal Orthopaedic Association Journal, 2024)
Sports-related injuries are rising correspondingly as sports become an increasingly integral part of life in developing countries like Nepal. Whether it’s the growing enthusiasm for football, cricket, volleyball, or traditional sports, more people, especially youth, are engaging in physical activities that expose them to potential injuries. While the benefits of sports in promoting health, social cohesion, and national pride are undeniable, the management of sports injuries in these contexts presents significant challenges.